Nonconvulsive Status Epilepticus: Current Status and Future Perspectives - Khanna, Laxmi; Agarwal, Nandini (International Journal of Epilepsy, 2021)
Introduction Nonconvulsive status epilepticus is defined as a state of impaired consciousness with subtle motor manifestations and ongoing seizure activity in the electroencephalogram (EEG) for at least 30 minutes.Objectives and Methods This study of nonconvulsive status epilepticus and its outcomes was a retrospective analysis of the continuous bedside EEG recordings of 100 patients over 2 years (Aug 2017–July 2019) at the Neurophysiology Department in Sir Ganga Ram Hospital, New Delhi. There were two groups of patients in the study comprising of adults (72) and children (28). A comparison between the two groups was made based on the clinical presentation, etiology, EEG, MRI findings, treatment, and the consequences.Results and Conclusions In adults, nonconvulsive status had a high mortality rate, while in children, the associated comorbidities dominated and contributed to residual neurological sequelae. Early diagnosis and treatment at any age is essential to prevent cognitive decline and psychomotor retardation. Presently, bedside and ambulatory EEG recordings are used to capture the dynamic and rhythmic features of the ictal EEG. Continuous EEG monitoring enables bedside assessment of the effectiveness of treatment.
Keywords: nonconvulsive status; Salzburg criteria; antiepileptics